The Research of Design Dynamics on Behavior Flow Ecosystem - Hao Yongtao; Chen Bihuan; Lou Diming (Institute of Advanced Engineering and Science, 2013)
We analyze the current product design modeling background and status, combined with the design dynamics, propose more intelligent design of the product behavioral modeling. by analogy Ecosystem, proposed the concepts and design framework product flow behavior and product behavior flow of the ecosystem. Proposed the concepts of design entropy flow and conservation in design dynamics, put forward a hybrid Petri nets to describe the flow behavior and formal product ecosystem model, a hybrid Petri net is given to the behavior flow ecosystem model and analyze engine and the design entropy. DOI: http://dx.doi.org/10.11591/telkomnika.v11i11.3552